PRIMARY EDUCATION IS A MODERN APPROACH TO PROBLEMATIC TEACHING OF MATHEMATICS LESSONS - Melibayev Anwar Rashidovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article focuses on a new system of rules governing the use of previously known methods of teaching and teaching, taking into account students' logical thinking options and the laws of students' research activities in problematic teaching of primary education mathematics classes, the development of more student thinking abilities, its general development and beliefs.